IMPLEMENTASI PEMBELAJARAN YANG EFEKTIF BAGI SISWA MADRASAH IBTIDAIYAH - Fitriani, Anisya (Sekolah Tinggi Agama Islam Negeri (STAIN) Curup, 2019)
Learning is an obligation for every believer to gain knowledge in order to improve the degree of life for them. To be able to absorb optimal learning, the application of effective learning is needed. This paper aims to provide information to educators on the effective learning concept, the concept of apperception and how to do apperception in creating effective learning. The apperception conducted in the early stages of learning is generally considered to be a small thing and sometimes forgotten that many learning activities leads to failure. The apperception can create effective learning because the apperception can lead learners to condition (zone) alpha, which is the best condition for learning so that learners more easily absorb the lesson material. The research method used is a qualitative method. The expected results of this paper are the achievement of effective learning for students so that the learning process can be optimized.